The Importance of Oil and Gas Pipelines in International Relations - Ghudhban, . Abathe (The Gulf Economist, 2025)
Energy security is considered one of the relatively modern components of national security. With industrial and technological advancements, energy has become the cornerstone of development plans for any country seeking real development and high growth rates, which are reflected in the economic performance indicators of the state. Energy pipelines form vital arteries for transporting natural resources from production sites to consumer markets, making them critical connection points between producing and consuming countries, as well as the transit nations through which these pipelines pass. Consequently, the significance of these pipelines extends beyond the economic aspect to the core of political and diplomatic interactions. They can serve as a means to enhance cooperation and partnership between nations or become a source of geopolitical conflicts and tensions. Since the discovery of oil and gas as primary energy sources, states have sought to secure their interests in this domain by building strategic partnerships or competing over resources.